2008
DOI: 10.2134/agronj2007.0361
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Nutrient Export of Grain Corn Fertilized with Raw and Treated Liquid Swine Manure

Abstract: Treatment of liquid swine manure (LSM) is an option to improve nutrient management. Mineral fertilizer, raw LSM, and LSM treated by anaerobic digestion, fl occulation, fi ltration, or natural decantation were sidedressed (100 kg N ha −1 ) to grain corn (Zea mays L.) on a clay and a loam soil. Over 3 yr, corn grain yield (6 to 11 Mg ha −1 ), N export (83 to 176 kg ha −1 ), and P export (19 to 40 kg ha −1 ) were similar among LSM types and between LSMs and mineral fertilizer. Th is was attributed to the immediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 27 publications
6
54
0
4
Order By: Relevance
“…Phosphorus accumulation in the upper soil layers is desirable, for being the region of concentrated thinner crop roots responsible for most of the nutrient and water uptake (Bortoluzzi et al, 2014), which is reflected in a greater quantity of P accumulated in the shoots and in DM production (Chantigny et al, 2008), as observed in oat and maize (Table 3). But on the other hand, part of the P accumulated in the upper soil layers can be transferred in soluble form in the runoff solution or adsorbed to particles, to surface waters adjacent to the cultivated area, increasing the risk of water eutrophication, which is undesirable (Ceretta et al, 2010b;Wang et al, 2013;Schmitt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus accumulation in the upper soil layers is desirable, for being the region of concentrated thinner crop roots responsible for most of the nutrient and water uptake (Bortoluzzi et al, 2014), which is reflected in a greater quantity of P accumulated in the shoots and in DM production (Chantigny et al, 2008), as observed in oat and maize (Table 3). But on the other hand, part of the P accumulated in the upper soil layers can be transferred in soluble form in the runoff solution or adsorbed to particles, to surface waters adjacent to the cultivated area, increasing the risk of water eutrophication, which is undesirable (Ceretta et al, 2010b;Wang et al, 2013;Schmitt et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The authors propose that the input of chemical fertilizers should decrease with the use of anaerobically digested residues, whereas soil texture is improved [90]. Chantigny and colleagues [91] reported similar fertilizer values of raw and anaerobically treated liquid swine manure to that of mineral fertilizer upon immediate incorporation into soil [91], supporting the significant potential of biogas residue as a valuable substitute and/or complement to mineral fertilizers. Moreover, the risk of postharvest NO 3 accumulation with swine manure was no higher than that with mineral fertilizer [91].…”
Section: Effects Of Biogas Residue On Plant Growthmentioning
confidence: 98%
“…The statements are deducted from the assumed better match of N supply and crop N demand, as a consequence of the higher ammonium-N/ total N share in digestates compared to the input feedstocks. However, several field studies have demonstrated that anaerobic digestion of animal manures do not affect soil mineral N content in autumn at the beginning of the main leaching period, meaning no differences in the nitrate leaching risk of digested in comparison to undigested animal slurries (Chantigny et al 2008;Merz and Trösch 1989;Möller and Stinner 2009;Pötsch 2005). However, implementation of biogas plants can be accompanied by several changes of the cropping system (crop acreage, cover cropping, etc.)…”
Section: Effects Of Anaerobic Digestion On Digestate Organic Matter Cmentioning
confidence: 99%